Comparatively evaluating the effects of exercising at the anaerobic threshold on oxidative stress and serum levels of leptin, nesfatin-1 and irisin in sedentary male and females - Ugras, Seda; Algul, Sermin; Ozdenk, Cagrı (Progress in Nutrition, 2022)
Study Objectives: Exercise has great impact on increases of energy metabolism and imbalance of oxidant antioxidant status. We aimed to analyse the relationships between exercise induced oxidative stress and energy regulatory hormones of leptin, nesfatin-1 and irisin in sedentary male and female subjects. Methods: Total of 30 subjects (15 male and 15 females) performed an aerobic exercise approximately 45 min. Blood samples were taken at baseline and at the end of the exercise. ELISA method used to analyse parameters of leptin nesfatin-1, irisin, total oxidant status (TOS) and total antioxidant status (TAS). Result: Exercise caused significant increase in levels of irisin and TOS but TAS level decreased in all subjects. In addition, leptin and irisin levels decreased significantly in female but they did not change significantly in males. Conclusion: Energy regulatory hormones did not correlate with the change of TAS and TOs levels. However, gender differences have great impact on energy regulatory hormones which needed to be evaluated in further studies.